Intervertebral disc deformation in the lower lumbar spine during object lifting measured in vivo using indwelling bone pins - Schmid, Stefan; Kramers-de Quervain, Inès; Baumgartner, Walter (Journal of biomechanics, 2024)
Object lifting is often categorized into squat and stoop techniques, with the former believed to protect the back by maintaining a neutral spine, and the latter considered harmful due to spinal flexion. Despite the widespread promotion of these beliefs, there is no evidence to support such dichotomy, as spinal flexion is not conclusively linked to low back pain. This study aimed to investigate intervertebral disc deformation in the lower lumbar spine during squat and stoop lifting using indwelling bone pins. Five healthy males underwent insertion of Kirschner wires into the L3, L4, and L5 spinous processes, followed by biomechanical data collection using magnetic and optical tracking systems during upright standing, isolated flexion/extension, and object lifting with both squat and stoop techniques. Except for one subject, stoop lifting resulted in up to 90 % greater disc wedging compared to squat lifting, with a significant difference at L4/L5 (p = 0.042). The anterior annulus fibrosus experienced 10 % to 40 % more compression during stoop lifting, but no significant differences were found in posterior annulus fibrosus expansion between techniques. Lever arms were about 35 % longer during stoop compared to squat lifting. These results indicate that even though stoop lifting generally led to greater disc deformation, significant deformation was also observed during squat lifting, challenging the notion of maintaining a neutral spine with this technique. Moreover, the considerable variability observed among participants raises concerns about the suitability of current one-size-fits-all lifting guidelines.